Analisa Perhitungan dalam Penerapan Konsep Distribusi Peluang Diskrit dan Statistika Deskriptif - Muhammad Taufiq Rachmat; Ranita Puspa Sari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
ABSTRACT This study aims to analyze calculations in the application of the concept of discrete probability distribution and descriptive statistics where the case study was conducted at the Medika Pratama Blanakan clinic by knowing the level of service and patient arrivals during the pandemic. The research method used is Statistics. The solution model in this study uses a discrete probability solution model and descriptive statistics. The results of the study, the two settlement models used for problem solving can be said to be in accordance with the research variables discussed and can be used as solutions and research recommendations properly. The calculations in this study were adjusted to the results of manual calculations and calculations with the help of SPSS applications or software and there was no difference in the calculation results between the two. Conclusion, Based on the discussion, calculation, and research that has been done at the Medika Pratama Blanakan Clinic as a case study location with the completion process using a statistical model in the settlement model, namely Discrete Probability and Descriptive Statistics, this can be completed properly according to the calculation flow. Keywords: Discrete Probability, Descriptive Statistics, Service Level